Conducta obstétrica en multípara de 30 años de edad embarazada de 36.2 semanas de gestación con óbito fetal - Moncada Mora, Kerly Aracely (2021)
This research addresses issues related to obstetric complications during pregnancy, childbirth and the puerperium, with an approach based on dystocia of presentation during premature twin birth that often ends in fetal death of one of the products. Twin pregnancy has a higher incidence of perinatal complications than single pregnancy and to demonstrate this, the clinical case of a 30-year-old patient is presented, in her 5th gestation, and like the previous ones, this would correspond to her fifth delivery. He does not refer to abortions or caesarean sections. She is currently carrying a twin pregnancy of 36.2 weeks of gestation, corroborated by F.U.M. 08/25/2020 where said patient goes to the Nicolas Cotto Infante basic hospital in the city of Vinces for contractile pain at the hypogastric level that radiates to the lumbosacral region of mild intensity of more or less 10 hours of evolution. The patient reports that she has undergone 4 check-ups throughout her pregnancy and no control ultrasound was performed. Upon arrival and upon being intercepted for obstetric evaluation, both fetuses had active movements, a 2cm dilation to the touch. Cervix in central position and the mucous plug has already been removed. She is subjected to labor which is hampered and interrupted in the presentation of the products, resulting in fetal hypoxia of one of the products.